[Shoreline at Eldfell] - Streng, Evelyn Fiedler (1975)
Photograph of shoreline at Eldfell. The black, rocky beach sits along the grey and white ocean to the left. Brown, sandy hills sit in the foreground and to the right covered in jagged brown rock. Several of the rock formations form jagged pillar-like structures. The photograph is blurry and dim under the grey cloud walls in the background.